Student Perceptions: Challenges and Opportunities of Using Grammarly on Thesis Writing - NIKMATUZ ZUHRIAH; MOHAMMAD FATONI; NANIN VERINA WIDYA PUTRI; MOH. ZAINUDDIN (English Department, Universitas Negeri Surabaya, 2024)
Writing skills in English are considered challenging, particularly in academic contexts like thesis writing, where effective organization and expression are crucial. Many students used Artificial Intelligence (AI) tools, such as Grammarly, to enhance their grammar, punctuation, and spelling. This research explored EFL students' perceptions of Grammarly in thesis writing, focusing on both the opportunities and challenges associated with its use and their responses to those. The study was conducted with final-year students at a reputable university who used Grammarly's free version, employing a qualitative design and using semi-structured interviews to get the data. Findings indicated that student perceptions of Grammarly were positive for its user-friendliness, instant feedback, and efficiency in addressing grammar, spelling, and punctuation errors. The opportunities identified include immediate feedback, consistent evaluation, additional correction insights, and improved writing efficiency, all contributing positively to thesis writing quality. However, challenges such as over-reliance on AI, the necessity for manual rechecking, limitations of the free version, difficulties with tense detection, and internet connectivity issues were also reported. Students generally appreciate Grammarly's suggestion in correcting grammatical and technical challenges but have varied responses to its challenges, with some continuing to use the tool despite its shortcomings and others using similar alternative options. Suggestions for further research include comparing Grammarly with other writing assistance tools in the context of thesis writing and using quantitative methods to better assess its effectiveness. Future studies could develop diverse research instruments to enrich the findings of this research.